Caracterização de fases magnéticas de solos de Roraima - Silva, Aduan Luiz da (2016)
The caracterization of phases magnetics in soils enables mineralogical knowledge, qualitative, quantitative and monitoring of constitution these soils in environment. As even can reveal important information about type of soil, iron diagnosis and its depth distribution, since this chemical elemente is directly linked to magnetism. The magnetic study this direction, has shown significant results of technological interest, agrarian, in climatic interpretations qualitatives of environment and the reconstruction of foremothers conditions environmental of a region. This study aims to characterize mineralogical of some Roraima soil, emphasizing the study of magnetics phases. Therefore samples were collected of four point different of status advanced weathering or little weathered soils. The analysis were performed from the application of techniques: fluorescence x-ray, x-ray diffraction combined with Rietveld method, and measures of magnetization for field and temperature. The analysis of DRX reveal prodominance of Fe, Si, Ti, Mn, K, V, Zn, Cu etc, in the samples. Analysis of DRX reveal the presence of the phases following : Albite, ankerite, bementite, kaolinite, clinoclore, spinel(Zn,Fe), hematite, hausmannite, ilmenite, maghemite, magnesiohornblend, magnetite, mantmorillonit, muscovite, nontronite, quartz, sodalite and spangolite. However, the major magnetic phase it is detected in soils of Cambissolo Háplico with (53,79%) in magnetite. The magnetizatiom of measureds show the presence of magnetics phases: magnetite, hematite e goethite. With values of magnetization and transition temperature characteristics of these phases. But with values depending on the type of soil, indicating different processes weathering. The hysteresis results indicate the presence of particles of hematite and/or goethite with pseudo-single domain (PSD), and magnetite and/or maghemite with multi domains (MD) e PSD.